Description of three new Amazonian species of Portanus (Hemiptera: Cicadellidae) from Brazil - Prando, Jádila Santos; Cavichioli, Rodney Ramiro; Takiya, Daniela Maeda (Zootaxa, 2025)
Three new species of the tribe Portanini are herein described and illustrated: Portanus kaonashi sp. nov. and Portanus haku sp. nov., from Mato Grosso State, and Portanus chihiro sp. nov., from Pará State, Brazil.